LAWSUITS CONCERNING PROFESSIONAL RESPONSIBILITY AT THE CLINICAL HOSPITAL “SISTERS OF MERCY” ZAGREB, KROASIA - , KREŠIMIR ROTIM (International Journal of Health Law and Government Policy, 2020)
In the Republic of Croatia there are no officially published statistical data about the number, reasons, procedures and results of lawsuits concerning the professional responsibility of hospitals, doctors and other medical staﬀ. So far, in Croatia there are published data about the number of claims for damages or charges only for Clinical Hospital “Sisters of Mercy” in one research work made in 2007, but it was unpretentious research in comparison to this research work. When this work was done, The Clinical Hospital “Sisters of Mercy” was the fourth biggest hospital in Croatia, with approximately 900 beds and 2500 employees. After fnishing this work, three smaller hospitals were integrated to our Hospital, due to process of reforming Croatian health system, and now our Hospital is the second biggest hospital in Croatia, with about 4,200 employees and about 1450 hospital beds. The folowing data does not incude data concerning three hospitals that were integrated to our Hospital in July 2010. The hospital annually provides ambulatory and diagnostic treatment for about 650 000 outpatients and treats about 42 000 inpatients. There are about 3200 deliveries annually in the maternity unit, and the surgical teams annually perform about 25 000 surgeries.The doctors working at the hospital cover almost all existing specializations. Because of the above reasons, the Clinical Hospital “Sisters of Mercy” is a showcase example for the statistics about lawsuits and settlements concerning professional responsibilities of doctors and other medical staﬀ in Croatia. This paper is focusing on the statistics of such legal procedures in the Clinical Hospital “Sisters of Mercy” from January 1 1967 until present day. According to the processed data there was an increase in the number of claims for damages in the mid-1990΄s. The curve has constantly been rising with oscillations. Based on the obtained data, it is possible to conclude the approximate number of the above mentioned legal procedures in Croatia,  and to observe other tendencies in that area.